Olfactory Dysfunction and Its Association With Neuropathologic Proteins in Cerebrospinal Fluid From Patients With Parkinson Disease - Guo, Peng; Wang, Rui-dan; Lian, Teng-hong; Ding, Du-yu; Zhang, Ya-nan; Zhang, Wei-Jiao; Li, Dan-ning; Li, Li-xia; Li, Jing-hui; Guan, Hui-ying; Yu, Shu-yang; Liu, Li; et al. (Frontiers in Aging Neuroscience, 2020)
Background and purpose Olfactory dysfunction (OD) is a common non-motor of Parkinson disease (PD). However, the relationship between OD and neuropathologic proteins in cerebrospinal fluid (CSF) from PD patients remains unclear. Methods Demographic variables of 166 PD patients were recorded. Overall olfactory function was assessed by summing up the scores of olfactory threshold, discrimination and identification by Sniffin’ Sticks Test, based on which, patients were divided into PD with OD (PD-OD) and PD with no OD (PD-NOD) groups. The levels of neuropathologic proteins, including α-Synuclein, Aβ1-42, total tau (T-tau) and multiple forms of phosphorylated tau (P-tau) in CSF were measured by enzyme linked immunosorbent assay. Results In 166 PD patients, 103 cases (62.0%) were with OD. The scores of overall olfactory functions, and olfactory threshold, discrimination and identification in PD-OD group were all significantly lower than that in PD-NOD group (P<0.001). α-Synuclein level in CSF was significantly higher in PD-OD group than PD-NOD group(P<0.05), and was significantly and negatively correlated with the scores of overall olfactory functions, and olfactory discrimination and identification (P<0.05). Aβ1-42 level in CSF was higher in PD-OD group than PD-NOD group, and was significantly and negatively correlated with olfactory identification score (P<0.05). T-tau level in CSF was significantly lower in PD-OD group than PD-NOD group(P<0.05), and was significantly and positively correlated with olfactory discrimination score (P<0.05). There was no significant difference in P-tau level in CSF between PD-OD and PD-NOD groups and no correlation between OD score and P-tau level in CSF. Conclusions PD-OD includes the impairments of olfactory threshold, discrimination and identification, and is associated with the significant elevation of α-Synuclein and decrease of T-tau level in CSF.